XXXIV Symposium on Hydroacoustics Jastarnia, Poland, May 23 – 26, 2017 - XXXIV Symposium on Hydroacoustics, Chronicle (Archives of Acoustics, 2017)
The paper contains the abstracts of papers presented during XXXIV Symposium on Hydroacoustics Jastarnia, Poland, May 23 – 26, 2017.